Diffusion of mepivacaine to adjacent synovial structures after intrasynovial analgesia of the digital flexor tendon sheath. (23rd May 2015) - Jordana, M.; Martens, A.; Duchateau, L.; Haspeslagh, M.; Vanderperren, K.; Oosterlinck, M.; Pille, F.
Summary: Reasons for performing study: Controversy exists about the specificity of diagnostic analgesia of the digital flexor tendon sheath (DFTS) in horses. Objectives: To evaluate the degree of diffusion of mepivacaine from the equine DFTS to adjacent synovial structures. Study design: Crossover experiment. Methods: Under general anaesthesia, the DFTS of one front and one hindlimb of 8 horses were injected simultaneously with mepivacaine. Synovial fluid samples of the injected DFTS, the adjacent metacarpo‐/metatarsophalangeal (MCP/MTP) joint, proximal interphalangeal joint, distal interphalangeal joint, navicular bursa and contralateral MCP/MTP joint were collected 15 min post injection (T15) from one of the injected limbs and 60 min post injection (T60) from the other limb. Venous blood samples were obtained at T0, T15 and T60 to evaluate systemic distribution of mepivacaine. After a 2‐week washout period, the procedure was repeated using the same limbs but reversing the time of sampling (front vs. hindlimbs). The concentration of mepivacaine in samples was measured with a commercial ELISA kit. Results: Mepivacaine concentrations in the DFTS samples, at both T15 (5077 mg/l) and T60 (3503 mg/l), exceeded those estimated sufficient to produce synovial analgesia (100 mg/l or 300 mg/l). Mepivacaine was found in all synovial structures adjacent to the injected DFTS and in the contralateral MCP/MTP joints, but concentrations were low, with a maximum value of only 3.2 mg/l. With the exception of the navicular bursa samples, the mepivacaine concentrations in the adjacent synovial structures were significantly higher at T60 than at T15 (P<0.03). Significantly higher mepivacaine concentrations were found in the ipsilateral than the contralateral MCP/MTP joints at T60 (P<0.001). Blood samples had significantly higher mepivacaine concentrations at T15 and T60 than at T0 (P<0.001). Conclusions: Mepivacaine injected into the DFTS of horses diffuses towards adjacent synovial structures without achieving clinically relevant concentrations.